Modelling scapular biomechanics to enhance interpretation of kinematics and performance data in rowing - Urbanczyk, C. A.; McGregor, A. H.; Bull, A. M. J. (ISBS Proceedings Archive (Michigan), 2019)
Rowing involves repetitive, high intensity loading on the glenohumeral joint. Shoulder pain is associated with muscle weakness and imbalance, resulting in long-lasting overuse injuries. The goal of this study was to explore three-dimensional shoulder biomechanics during rowing to identify parameters that influence technique. Eleven athletes had their movement recorded by motion capture while using an instrumented ergometer. Kinetics and kinematics drove a computational model which output joint and muscle forces across the shoulder. Results suggest that subtle muscular changes identified by the model can be sensitively mapped to performance variables. When evaluated alongside ergometer-derived power metrics, biomechanics parameters can provide athletes and coaches a fuller picture of performance potential, injury risk, and training program efficacy.